2019
DOI: 10.5114/amscd.2019.86742
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IMP and VIM genes in Pseudomonas aeruginosa isolated from Egyptian patients

Abstract: Introduction: Metallo-β-lactamase production among Pseudomonas aeruginosa is a major health problem worldwide. Pseudomonas aeruginosa acquire several mechanisms of resistance towards carbapenems through the production of metallo-β-lactamases, especially VIM and IMP. The problem of multi-drug-resistant Pseudomonas aeruginosa is increasing all over the world, reaching dangerous levels. The aim of this study was to detect the metallo-β-lactamases bla VIM and bla IMP genes in Pseudomonas aeruginosa strains in Suez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Our findings are comparable to a previous report from Egypt, where bla NDM-1 was the main MβL (90.9%), followed by bla VIM-1 (18.1%), 9 whereas bla IMP was not detected, as in another previous study which reported its low rate, 33 while other studies did not find it at all. 9 , 20 , 34 This is in contrast to other parts of the world, such as Iran and China, where bla IMP is the prevailing MβL in P. aeruginosa . 35 , 36 The occurrence of bla VIM in a carbapenem-sensitive isolate was also previously documented from our healthcare setting by another study.…”
Section: Discussionmentioning
confidence: 82%
“…Our findings are comparable to a previous report from Egypt, where bla NDM-1 was the main MβL (90.9%), followed by bla VIM-1 (18.1%), 9 whereas bla IMP was not detected, as in another previous study which reported its low rate, 33 while other studies did not find it at all. 9 , 20 , 34 This is in contrast to other parts of the world, such as Iran and China, where bla IMP is the prevailing MβL in P. aeruginosa . 35 , 36 The occurrence of bla VIM in a carbapenem-sensitive isolate was also previously documented from our healthcare setting by another study.…”
Section: Discussionmentioning
confidence: 82%
“…The infection control practises and strategies followed in hospitals influence the MβLs that produce P.aeruginosa in Egypt [16] . According to the current study, Carbapenem resistance was observed in 65% of P. aeruginosa clinical isolates against (imipenem and meropenem).…”
Section: Discussionmentioning
confidence: 99%
“…That is nearly similar to Khorvash et al 2 results where IMP and VIM genes were detected in 31.3% and 14.6% of the isolates, respectively and Yousefi et al 21 results that 17.31% of CRPA had VIM gene. While Kazeminezhad et al 22 documented that 31.5% and 10.5% of the isolates had respectively VIM and IMP gene alone .Here in, both IMP and VIM genes and mostly present in wound isolates (27.3%) that differs from results EL Maraghy et al23 study that the IMP gene was not expressed in any strain and the VIM gene was present at the highest level in blood specimens.Regarding biofilm quantification analyses, 81.9%, 13.6%, 4.5% of P. aeruginosa C.I.s were strongly, moderately, weakly adherent and 29.1% were non adherent that higher than that by Lima et al4 where 10%, 25%, 40% were strongly, moderately and weakly adherent, and 25% were non-adherent and that by Perez et al 24 who recorded that 4% of P. aeruginosa C.I.s were moderately adherent and 96% were weakly adherent. Fattouh et al16 study recorded that 17%, 19% and 22% of P. aeruginosa C.I.s were strongly, moderately and weakly adherent respectively.…”
mentioning
confidence: 85%